Fairy Tale Therapy as an Interdisciplinary Field of Research (Based on the Results of a Discussion Held at the Russian State Library) - I.V. Mersianova; M.V. Mersiyanova (Клиническая и специальная психология)
On June 26, 2024, as part of the program of the XIII International Summer School “Evolution of Institutions for Self-Organization and Charity”, the Russian State Library for Young Adults held a discussion on "How to Form Positive Attitudes towards Philanthropy and Mutual Assistance?", which was attended by civil society researchers from Russia, Kazakhstan, Tajikistan, Belarus, Romania and the United Arab Emirates. The lively discussion focused on the methodology for using fairy tale therapy as a specific area of practical psychology to solve many social and cultural problems. In particular, the following question was highlighted: How fairy tales help develop social empathy, promote philanthropy in society and promote unity among people, and form attitudes towards charity and mutual assistance.